Oral bioaccessibility of inorganic contaminants in waste dusts generated by laterite Ni ore smelting - Ettler, Vojtěch; Polák, Ladislav; Mihaljevič, Martin; Ratié, Gildas; Garnier, Jérémie; Quantin, Cécile (Environmental geochemistry and health, 2018)
The laterite Ni ore smelting operations in Niquelândia and Barro Alto (Goiás State, Brazil) have produced large amounts of fine-grained smelting wastes, which have been stockpiled on dumps and in settling ponds. We investigated granulated slag dusts (n = 5) and fly ash samples (n = 4) with a special focus on their leaching behaviour in deionised water and on the in vitro bioaccessibility in a simulated gastric fluid, to assess the potential exposure risk for humans. Bulk chemical analyses indicated that both wastes contained significant amounts of contaminants: up to 2.6 wt% Ni, 7580 mg/kg Cr, and 508 mg/kg Co. In only one fly ash sample, after 24 h of leaching in deionised water, the concentrations of leached Ni exceeded the limit for hazardous waste according to EU legislation, whereas the other dusts were classified as inert wastes. Bioaccessible fractions (BAF) of the major contaminants (Ni, Co, and Cr) were quite low for the slag dusts and accounted for less than 2 % of total concentrations. In contrast, BAF values were significantly higher for fly ash materials, which reached 13 % for Ni and 19 % for Co. Daily intakes via oral exposure, calculated for an adult (70 kg, dust ingestion rate of 50 mg/day), exceeded neither the tolerable daily intake (TDI) nor the background exposure limits for all of the studied contaminants. Only if a higher ingestion rate is assumed (e.g. 100 mg dust per day for workers in the smelter), the TDI limit for Ni recently defined by European Food Safety Authority (196 µg/day) was exceeded (324 µg/day) for one fly ash sample. Our data indicate that there is only a limited risk to human health related to the ingestion of dust materials generated by laterite Ni ore smelting operations if appropriate safety measures are adopted at the waste disposal sites and within the smelter facility.
Keywords: Administration, Oral; nikl; Nickel; Brazil; Dust; žaludeční šťáva; Metallurgy; Gastric Juice; aplikace orální; anorganické látky; popel uhelný; Coal Ash; Models, Biological; nebezpečný odpad; průmyslový odpad; kobalt; Brazílie; Hazardous Waste; lidé; prach; biologické modely; Humans; Refuse Disposal; Industrial Waste; Environmental Exposure; Cobalt; odpadky - odstraňování; hutnictví; chrom; Inorganic Chemicals; Chromium; vystavení vlivu životního prostředí